IMPLIKATUR PERCAKAPAN DALAM TRANSAKSI JUAM BELI DI UJUNG SURAMADU MADURA - Annisa Fajar Aprilia; Ira Eko Retnosari (Buana Bastra, 2018)
This research is based on the occurrence of conversation implicature transactions in buying and selling transactions at the end of Suramadu Madura. Implications in conversation are conventional forms of implicature and unconventional implicatures. This research is a kind of conversational implicature in a sale and purchase transaction at the end of Suramadu Madura. This method is a descriptive method. The purpose of this study is to describe the pattern of systematic, factual and accurate relationships between the phenomena investigated. Implicit in the sale and purchase transaction at the end of Suramadu Madura has two types, namely: conventional implicature and unconventional implicature. Conventional Implication is a type of implicature derived from the meaning of words, not from the principle of conversation. Whereas nonconventional implicatures are the implications of pragmatics implicit in conversation. In communication, speech always presents functional functions and in conversation, intentions implied.